Blood on the trail [large type] - McCauley, Terrence (A Jeremiah Halstead western, 2022)
"Silver Cloud, Montana. A mining town welcome to all seeking to make their fortune. And a place where a lawman has to watch his back before some hardcase empties his pistol into it. Deputy U.S. Marshal Jeremiah Halstead is escorting notorious outlaw John Hudson across the territory for trial when he's ambushed by a pack of Hudson's men anxious to rescue their partner from his custody. Halstead puts the blast on them, but outnumbered and outgunned, he has little choice but to hole up in an old mining town known as Silver Cloud, Montana. It's a place where he can keep a lock on his prisoner while figuring out how to get past Hudson's gang alive. But the folks in Silver Cloud are none too happy playing host to the lawman or his kill-crazy prisoner. Unable to trust the sheriff to back his play, Halstead finds himself standing alone against Hudson's gang as they slip into town, recruiting gunmen to help free their leader. Except for Ed Zimmerman. He's spent his whole criminal life in John Hudson's shadow. He wants Hudson dead and buried so he can become the leader of the gang. And if he must, he'll put everyone in Silver Cloud six feet under--including Deputy U.S. Marshal Halstead . . ."--